Esterification of Fatty Acid Using Porcine Pancreas Lipase - Mohan Kumar, C.; Annapurna Devi, N.; Narasimha Rao, M. (Asian Journal of Chemistry, 2010)
The esterification of a long-chain fatty acid was conducted using porcine pancrease lipase in a mainly anhydrous non-polar organic medium, heptane. Propyl laurate was produced from lauric acid and n-propanol. The present study was confined to optimize the effect of the parameters, temperature, substrate concentration and the enzyme concentration on the esterification process. It was found that maximum yields were possible at 35°C, 0.75 M substrate concentration (the substrates being taken at equimolar quantities) and at 40 mg/mL enzyme concentration. Specific studies with these parameters show a maximum conversion with respect to increase in temperature and substrate concentration. As regards the effect of enzyme concentration on percentage conversion beyond 40 mg/mL concentration, the increase in per cent conversion was not very significant. Kinetic data were collected with optimum temperature and optimum enzyme concentration for each substrate concentration and it was found that the data obey Michaelis-Menton kinetics. The Km and Vmax values were found to be 4.185 g mol/L and 625 mmol/h-L respectively.